IMPLEMENTASI ALAT PERAGA OPERASI BILANGAN BULAT BAGI GURU SEKOLAH DASAR (SD) SE-KECAMATAN ILIR BARAT I PALEMBANG - Putri, Ratu Ilma Indra (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2011)
The purpose of this activity is to increase the ability of teachers in 1) make mathematics manipulative as a media of operations of integer, 2) used mathematics manipulative is made in classroom simulation. Method of the activities performed is a demonstration, presentations and discussion. The participants of this activity are 25 teachers of “Kecamatan Ilir Barat I